Judicial Independence and Dual Positions: A Siyasah Qadhaiyah Analysis of Constitutional Court Decision No. 183/PUU-XXII/2024 - Muhammad Rafi Sulistio; Muhammad Amin; Lutfi Fahrul Rizal (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This research is motivated by the limited number of studies analyzing Constitutional Court Decision No. 183/PUU-XXII/2024 concerning the prohibition of concurrent positions between leaders of advocate organizations and state officials from a siyasah qadhaiyah perspective. Previous studies generally focused on the constitutional aspects of the advocate profession without linking them to Islamic judicial principles. This research uses a normative juridical method with a statutory and conceptual approach through an analysis of Constitutional Court decisions, related regulations, and legal literature. The results show that the Constitutional Court affirms independence, impartiality, and the prevention of conflicts of interest as the primary basis for limiting concurrent positions to maintain the integrity of the advocate profession. This decision strengthens the professionalism of advocate organizations, clarifies the boundaries of relations with state power, and supports an accountable judicial system. From a siyasah qadhaiyah perspective, the decision aligns with the principles of justice, trustworthiness, and sadd al-dzari'ah as preventive mechanisms to maintain the purity of the judicial function. These findings confirm that Constitutional Court decisions have constitutional and normative relevance in developing a judiciary with integrity.